(entre)laços e nós: a constituição do campo acadêmico em política e gestão da educação no Nordeste do Brasil - Guimarães, Isac Pimentel (2016)
This study investigated the relationship between the standards of scientific production and the academic formation policy, through the struggles generated between the different positions of agents in collaborative networks, in the field of Education Policy and Management in the Postgraduate Programs in Education from the Northeast Region of Brazil, in the period of fifteen years (2000-2014). Thereunto, supported by the sociological doing and by the scientific field theory of Pierre Bourdieu, the emphasis reflects on the agent that produce an academic representation about the theme of scientific and institutionalized character, as well as the social the conditioning of its practice. The agents inside such a space, endowed with a disposition system, with specific competencies, different species of capital and its interests, confront each other in the struggle to legitimize certain conception of local and regional theme; which is, above all, a way of vision of the academic social world. Methodologically, it sought to establish the structure of the academic production space, through the use of statistical tools, the factory analysis of multiple correspondences and analysis of social networks, in order to objectify and, thereby, to identify the pathway of academic-professional formation of the agents, the organization of scientific collaboration networks, based on bibliographical production of articles, books and chapters in books, as well as, from semi-structured interviews, to observe the materialization of academic space, through interknowledge and the process of legitimization among peers, evidencing thus the position of academic elites in the space of knowledge production in the Education Policy and Management, its organization strategies - individual and group - and establishment of scientific production schedule. From the results obtained in general characterization of the agents' profile, we verified that most of them are female, with academic formation (degree in pedagogy, master's degree in education and doctorate in education) in the Northeast itself, linked to the reduced access to foreign research centers to accomplish the post-doctoral and/or the research trainee, they are neither productivity scholar from CNPq. For the jobs at SBPC, ANPEd and ANPAE, we noticed that the only programs that presented higher frequencies for the presence of these situations were at PPGE/UFPE, PPGE/UECE and PPGE/UFRN. On the other hand, they have an average time of nineteen years of career in public university performing, essentially, in research and teaching, although they participate of scientific journals committees and provide advisory service to the Ministry of Education. The hypotheses initially raised reinforce the thesis of the formation of academic elites and reference groups in the space of knowledge production in Education Policy and Management that contribute to the engendering of legitimate social practices around the game for imposition of speeches about educational policy, academically valid in the context of intensification of the regional asymmetries.